Learn to draw now! - DuBosque, Doug (Molalla, OR Peel Productions, 1991)
Introduces techniques and exercises for rendering the basic three-dimensional forms essential for realistic drawing: the cylinder, cone, sphere, and box
Includes index
1
Keywords: Arts (drawing)